2012
DOI: 10.1603/me11172
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analysis of Xenopsylla cheopis (Siphonaptera: Pulicidae) Suggests a Role for Reactive Oxygen Species in Response to Yersinia pestis Infection

Abstract: Fleas are vectors for a number of pathogens including Yersinia pestis, yet factors that govern interactions between fleas and Y. pestis are not well understood. Examining gene expression changes in infected fleas could reveal pathways that affect Y. pestis survival in fleas and subsequent transmission. We used suppression subtractive hybridization to identify genes that are induced in Xenopsylla cheopis (Rothschild) (Siphonaptera: Pulicidae) in response to oral or hemocoel infection with Y. pestis. Overall, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…Recently, it was shown that ROS (H 2 O 2 ) levels in midgut were higher (over 10 mM) in Y. pestis infected fleas. Antioxidant treatment prior to infection decreased ROS levels and resulted in higher Yersinia pestis loads [64]. An OxyR Y. pestis mutant showed reduced growth in fleas early after infection [64].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was shown that ROS (H 2 O 2 ) levels in midgut were higher (over 10 mM) in Y. pestis infected fleas. Antioxidant treatment prior to infection decreased ROS levels and resulted in higher Yersinia pestis loads [64]. An OxyR Y. pestis mutant showed reduced growth in fleas early after infection [64].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant treatment prior to infection decreased ROS levels and resulted in higher Yersinia pestis loads [64]. An OxyR Y. pestis mutant showed reduced growth in fleas early after infection [64]. ROS are potentially toxic for both the host cell and pathogenic bacteria [16], [65], [66], [67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, factors that contribute to resistance to infection or elimination of Y. pestis within the flea may be downregulated or altered in function at lower temperatures. In a recent study, genes identified as being involved in the production of reactive oxygen species in response to Y. pestis infection in X. cheopis fleas (Zhou et al 2012) may be less active or nonfunctional at lower temperatures. Toxic degradation products derived from the flea blood meal and from which Y. pestis is thought to be protected via expression of ymt, encoding a phospholipase D required for survival of Y. pestis in the flea, may be less abundant in fleas maintained at low temperatures, thus reducing exposure of Y. pestis to these compounds (Hinnebusch et al 1998).…”
Section: Low-temperature Transmission Of Y Pestismentioning
confidence: 99%
“…Although flea gene expression has been investigated by a few groups (Dreher-Lesnick et al, 2010;Zhou et al, 2012), flea immunology remains overlooked. Yersinia pestis, the agent of plague, regulates gene expression in both fleas and mammals (Vadyvaloo et al, 2010).…”
Section: Kissing Bugs Sandflies and Fleasmentioning
confidence: 99%